The Drunken Duchess of Vassar : Grace Harriet Macurdy, pioneering feminist classical scholar - McManus, Barbara F., 1942-; Hallett, Judith P., 1944-; Stray, Christopher (Columbus : The Ohio State University Press, 2017)
In this biography, Barbara McManus recovers the intriguing life story of Grace Harriet Macurdy (1866-1946), Professor of Greek at Vassar College and the first woman classicist to focus her scholarship on the lives of ancient Greco-Roman women. Fondly known as "the Drunken Duchess," although she never drank alcohol, Macurdy came from a poor family with no social, economic, or educational advantages. Moreover, she struggled with disability for decades after becoming almost totally deaf in her early fifties. Yet she became an internationally known Greek scholar with a long list of publications and close friends as renowned as Gilbert Murray and John Masefield. Through Macurdy's eyes and experiences, McManus examines significant issues and developments from the late nineteenth to the mid-twentieth century, such as the opening of higher education to women, the erosion of gender and class barriers in the professions, the delicate balancing act between personal and professional life required of women, the marginalized role of women's colleges in academic politics, and changes in the discipline and profession of Classics in response to the emerging role of women and new social conditions.
The Drunken Duchess: a woman of contrasts -- Family and childhood -- From the Annex to Vassar -- Teacher and scholar -- Embattled -- Soldiering on -- Setting a course -- Unconventional families -- Fighting for justice -- Redefining the classical scholar as a woman -- Retirement: "Now begin the folio."
Includes bibliographical references (pages 267-274) and index.
Online resource; title from PDF title page (EBSCO, viewed January 31, 2017).
JSTOR
Keywords: Macurdy, Grace Harriet; Macurdy, Grace Harriet; Macurdy, Grace Harriet; Women classicists -- United States -- Biography; Femmes spécialistes de lettres classiques -- États-Unis -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; LITERARY CRITICISM -- Ancient & Classical; LITERARY CRITICISM -- General; Women classicists; United States; Electronic books; Biographies